COVID 19 and Indian Banking Sector – An Overview - Chandran, Salini R; Alamelu, K . (International Journal of Recent Advances in Engineering and Technology, 2021)
COVID 19, which is emerged as a black swan event of the century with significant macroeconomic impact both globally and in India. Due to this pandemic, people lost their jobs, and they can’t save anything, and they find it is difficult to live a standard life. The ongoing spread of the Covid-19 pandemic is disrupting the way banks operate. Banks are experiencing liquidity crunch, funding challenges, changing operating models and exposure to fraud, misconduct, and noncompliance due to COVID 19. The COVID-19 pandemic could be the most serious challenge to financial institutions. As the economic fallout spreads, banks find themselves juggling some big priorities that requires concrete steps to reposition now while also recalibrating for the future. They’re working to keep their distribution channels open, despite social distancing advice and supervisory and compliance functions that were never designed for remote work. Banks are suffering a lot to manage revenue and meet customer expectations and need to keep an eye on strategy and brand issues that will define their future, as market forces and customer behaviors potentially change coming out of this crisis. The credit management system of banks mainly affected with this pandemic. Banks asset quality worsens day by day, NPA are increasing and credit cost also increasing at a higher level. In order to revive from these banks need to promote digital banking services more among its customers rather than physical visit to the banks. So all the banking services can be provided to the customers without any loss. Apart from the above RBI also announced relief package by changing asset classification and provisioning norm and through injecting liquidity in the market.